ANALISA PENYEBAB TURUNNYA PRODUKSI KOPI ROBUSTA KABUPATEN TEMANGGUNG - Berliana Anggun Septiani; Istiarsi Saptuti Sri Kawuryan (EKUITAS (Jurnal Ekonomi dan Keuangan), 2021)
Indonesia has a potency in the coffee sector. Many robusta coffee farmers really depending on the coffee sector. For the example, 75% of coffee farmers in Temanggung Regency work in the robusta coffee sector. Fluctuations and declining coffee production can be a burden for coffee potency optimization and decreasing the income of the coffee farmers. This study aims to determine the factors that can affect the declining of Robusta coffee production in Temanggung Regency. The analytical methods used in this study are Value Chain Analysis, Forward Linkage and Backward Linkage, and Fishbone Analysis. The author is using secondary and primary data. Secondary data was obtained from Statistics Indonesia and Directorate General of Plantations at the Ministry of Agriculture.Primary data was obtained from interviews with 3 key informans Robusta coffee farmers in Gesing Village who eligible. The result showed that age of plants and distance of each plants, lack of coffee picking services, weather and lack of cooperation and other sectors, such as the trade sector and the industrial sector can lead into a decreasing of coffee production.